Proteasome Activity in the Plasma as a Novel Biomarker in Mild Cognitive Impairment with Chronic Tinnitus - Yun, Yejin (J Alzheimers Dis, 2020)
BACKGROUND: Although the existence of proteasomes in human blood, termed circulating proteasomes (c-proteasomes), has been reported previously, their origin and pathophysiological functions remain largely unknown. OBJECTIVE: Given that c-proteasome activity was significantly reduced in Alzheimer’s disease model mice and relatively high frequency of mild cognitive impairment (MCI) is accompanied by chronic tinnitus in aged patients, we examined whether c-proteasome activity in human plasma was associated with cognitive function in patients with chronic tinnitus. METHODS: c-Proteasome activity in the plasma of tinnitus patients (N = 55) was measured with fluorogenic reporter substrate, suc-LLVY-AMC. To assess MCI, the Montreal Cognitive Assessment was conducted with a cut-off score of 22/23. All patients underwent audiological and psychoacoustic analyses. Levels of c-proteasomes, Aβ(42), and Aβ(40) were measured using ELISA, and their association with c-proteasome activity was evaluated. RESULTS: The activity of circulating proteasomes was significantly lower in patients with chronic tinnitus and MCI (p = 0.042), whereas activities of other plasma enzymes showed little correlation. In addition, c-proteasome activity was negatively associated with the level of plasma Aβ and was directly dependent on its own concentration in the plasma of patients with chronic tinnitus. CONCLUSION: Our current work provides a new perspective for understanding the potential relationship between circulating proteasomes in the plasma and cognitive dysfunction, suggesting a novel, non-invasive biomarker in the context of MCI diagnosis.